PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH BERBANTUAN WORDWALL TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS IV SDI AL-IKHLAS - Eva Dwi Lestari; Alik Mustafidal Laili (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study addresses the issue of low cognitive achievement among students, which is attributed to the use of conventional, teacher-centered instructional methods and the limited integration of learning media. To address this challenge, there is a need for innovative instructional approaches that are active, interactive, and engaging. The purpose of this study is to investigate the effect of the cooperative learning model Make A Match assisted by Wordwall on the IPAS learning outcomes of fourth-grade students at SDI Al-Ikhlas. This research employs a quantitative approach with a quasi-experimental design, specifically the nonequivalent control group design. The study involves two groups: Class IV-A as the control group and Class IV-B as the experimental group. Pretest and posttest assessments, consisting of multiple-choice questions, were used to evaluate students’ cognitive learning outcomes in the domains of C1, C2, and C4. Data analysis included validity and reliability tests, item discrimination, difficulty level analysis, normality and homogeneity tests, and hypothesis testing using an independent sample t-test. The findings reveal that the implementation of the Make A Match model supported by Wordwall significantly improved the learning outcomes of students in the experimental group, as indicated by higher average posttest scores and a significance value of p < 0.05. Therefore, it can be concluded that the Make A Match cooperative learning model, when integrated with Wordwall, has a positive and significant impact on enhancing students’ IPAS learning achievement.